Facilitators and barriers to contraceptive uptake and use: Perspectives of female students in South Africa and lessons for quality provision of HIV pre-exposure prophylaxis - Patience Shamu; Nicola J. Christofides; Saiqa Mullick (PLoS ONE, 2025)
Young women in South Africa face a dual risk of unplanned pregnancies and HIV infections. The country’s high contraceptive prevalence rate masks underlying challenges affecting the initiation and maintenance of contraceptive use. Options are freely available at public health clinics and most women in the country use long-acting injectable contraceptives. Young women’s experiences of contraceptive services provide a unique opportunity to learn lessons for long-acting HIV Pre-exposure prophylaxis (PrEP). The paper aims to explore facilitators and barriers to using contraceptives among young female students to inform the delivery of long-acting PrEP. A qualitative study was conducted in one district in Gauteng province of South Africa. We purposively selected female students 18–24 years seeking sexual and reproductive health services (SRH) through fixed or mobile clinics in 2022 on two campuses. We conducted 22 in-depth interviews and five Focus Group Discussions (FGDs). Data were thematically analysed using NVivo 12 software. Individual-related barriers were mainly related to the side effects of contraceptives. At a family level, mothers sometimes played a supportive role which enabled continued contraceptive use, yet partners’ concerns about side effects were sometimes a barrier. Health systems-related issues included negative health provider attitudes and unfavourable opening hours. Accessing contraceptives over holidays when students travelled was a challenge. Long-acting injectable PrEP may be compatible with injectable contraceptives and could provide an opportunity to align visits. Training service providers on the importance of detailed information on side effects will be crucial. Promoting PrEP among mothers and partners could increase support for continued PrEP use. These lessons can be applied to delivering new long-acting HIV PrEP products near the market.